A method of accelerating CNN computation on DSP. (November 2020) - Li, Bin; Luo, Ying-guang; Guo-bin Fu, Luo; Peng, Ye; Hu, Jia
Abstract: Because convolution network contains a lot of multiplication and addition operations, there is still room for optimization after it is implemented on the hardware platform. This paper mainly studies the method of accelerating the deep learning algorithm on DSP, proposes to improve the convolution layer calculation by using Winograd algorithm, and implements it on GPDSP. The final results show that it can increase the parallelism of data calculation and significantly reduce the computing time.